A comparison of methods to determine maximal accumulated oxygen deficit in running - Bosquet, L.; Duchene, A.; Delhors, P. R.; Dupont, G.; Carter, H. (Journal of Sports Sciences, 2008)
The aim of this study was to compare maximal accumulated oxygen deficit (hereafter O2 deficit) estimated from the methods of Whipp et al. (1986), Medbo et al. (1988), and Hill et al. (1998) to determine whether they agree sufficiently to be used interchangeably. Nineteen moderately to highly trained endurance runners first performed an incremental test to exhaustion for the determination of maximal oxygen uptake (VO2max) and peak treadmill speed, followed by six randomly ordered constant-speed tests at 95, 100, 105, 110, 110, and 120% of peak treadmill speed. All tests were separated by at least 72 h and were performed within 4 weeks. The method of Whipp produced an O2 deficit estimate that was lower than that derived from the method of Hill or Medbo (bias ± 95% limits of agreement: -29.6 ± 36.6 and -26.1 ± 32.8 ml/kg, respectively; P < 0.001). The O2 deficit did not differ between the methods of Hill and Medbo (bias ± 95% limits of agreement: 3.5 ± 41.6 ml/kg; n.s.). However, poor correlations (0.21 < r < 0.33; n.s.) together with wide limits of agreement between O2 deficit estimates (70 - 80% of the mean response) clearly question using these methods interchangeably.